A prospective observational study of acute traumatic coagulopathy in traumatic bleeding from the battlefield. (1st June 2020) - Woolley, Tom; Gwyther, Robert; Parmar, Kiran; Kirkman, Emrys; Watts, Sarah; Midwinter, Mark; Lucca, Juandir Dalle; Hunt, Beverley J
Abstract : BACKGROUND: Acute trauma coagulopathy (ATC) after military trauma has not been comprehensively studied. ATC is defined as a prolonged prothrombin time ratio (PTr) or reduced clot amplitude (A5) in viscoelastic testing. Compared to civilian trauma, military trauma has more injuries from explosions and gunshot wounds (GSWs), potentially leading to a different pathophysiology for traumatic coagulopathy. This study aimed to characterize military ATC on admission to a military hospital in Afghanistan and to explore any differences due to the mechanism of injury. METHODS: Severely injured military casualties were enrolled in the study. Blood samples were taken on admission and after routine testing, waste plasma was prepared, frozen, and transported to the United Kingdom for in‐depth hemostatic analysis. RESULTS: Seventy‐seven percent of casualties had ATC defined by a PTr greater than 1.2 and 19% when defined by rotational thromboelastometry (ROTEM) A5 less than 36 mm. Coagulation factor depletion correlated with degree of shock, particularly factor V (p < 0.01), factor X (p < 0.01), and fibrinogen levels (p < 0.01). Thrombin generation was well preserved. Fibrinolytic biomarkers were raised correlating with the degree of shock (p < 0.01), and 8% of casualties had hyperfibrinolysis on ROTEM analysis. Plasmin‐antiplasmin complexes (p < 0.01) and d ‐dimer levels (p = 0.01) were higher and clot firmness lower (p = 0.02) in those injured by explosion compared to GSW's. CONCLUSIONS: ATC was present and correlated with shock, similar to civilian trauma. Thrombin generation remained adequate. Fibrinogen and factor V levels were disproportionately low but still sufficient to allow clot formation. Fibrinolysis is a key feature, probably due to a tissue plasminogen activator surge at the time of injury. Blast injuries are associated with a greater activation of fibrinolysis than GSWs.